Transformational teacher leadership and strategies for autonomous work in Peruvian students from a university from Peru - Campos-Pérez, Rosalvina (2023)
The objective of this research was to determine the relationship between transformational leadership teacher and the autonomous work strategies of university students from a university of Peru. The research was correlational and the design was non-experimental. The technique used was the survey and a questionnaire was applied using Microsoft Forms. The universe was constituted by the students of the faculties of Humanities and Architecture and Urbanism enrolled in the year 2022 at the Federico Villarreal National University Nacional. A convenience sample was used. Transformational leadership was worked with the Leadership Styles Questionnaire (CELID - A) and the Autonomous Work Strategies Questionnaire (CETA) was used to measure autonomous work. The analysis of the results indicates the following: Cronbach's alpha obtained a value of 0.970, which denotes high levels of reliability in the instrument developed. The sample was made up of 61.5% women and 38.5% men, whose ages ranged from 18 to 26 years. Regarding transformational teacher leadership, students value the feedback offered by their teachers. Regarding autonomous work strategies, the students state that they are not very familiar with their use and need to know various tools to develop them.